Revenue diversification and bank profitability: study on Indonesian banks - Muhammad Zaki Ashyari; Rofikoh Rokhim (Jurnal Siasat Bisnis, 2020)
Bank has traditional activities that generate interest income, and non-traditional activities such as underwriting and trading securities, broker-agent, and investment banking, and other activities that generate non-interest income. This paper investigates traditional and non-traditional activities and the impact of revenue diversification on bank profitability. We use the data from the Indonesia banking industry 2007-2016 to measure the impact of revenue diversification, commission revenue, trading revenue, and other revenue on bank return on asset and return on equity. We find that revenue diversification increases bank profitability. However, all the non-interest income has a negative correlation on bank profitability.